Using STEAM and Bio-Inspired Design to Teach the Entrepreneurial Mindset to Engineers - Bosman Lisa; Shirey Katherine L. (De Gruyter, 2023)
The need for addressing global and societal problems is stronger than ever, as demonstrated by the UN Sustainable Development Goals and National Academy of Engineering Grand Challenges. However, engineering undergraduate students rarely get to experience engaging with the associated real-world projects and challenges. This has the potential to result in attenuation from engineering education and career pathways. This study aimed to overcome this issue by reaching the United States' untapped future engineering workforce via an engineering educator professional development "train-the-trainer" program. This train-the-trainer program guided engineering educators to apply evidence-based pedagogical methods (e.g., backward course design) to couple entrepreneurial mindset (EM) development with STEAM (science, technology, engineering, arts, math) and bio-inspired design in an effort to improve the retention of underrepresented engineering students via a transdisciplinary, humanistic approach. This study employed a mixed methods approach including retrospective post-then-pre items based on perceived learning gains, rating the overall satisfaction with the program, and open-ended questions to better understand what went well, what did not go so well, and what can be improved. From a practical perspective, this study shows that integrating STEAM (with a specific focus on the arts) into the engineering classroom promotes problem-solving and critical thinking across disciplines. Here, applying STEAM principles encourages diverse perspective taking and making by bridging paradigms and theoretical frameworks across a variety of humanities and technical disciplines. As a result, combining STEAM with bio-inspired design and the EM has the capacity to increase engagement and broaden participation among students traditionally underrepresented in engineering, including females and minoritized populations.